2020
DOI: 10.1177/0885328220977605
|View full text |Cite
|
Sign up to set email alerts
|

Surface functionalized mesoporous silica nanoparticles for intravitreal application of tacrolimus

Abstract: Tacrolimus (TAC), a potent immunosuppressive macrolide, has been investigated for ocular diseases due to promising results in the treatment of anterior and posterior segments eye diseases. Mesoporous and functionalized silica nanoparticles show potential as TAC delivery platforms owing to their interesting characteristic as large surface area, uniform pore size distribution, high pore volume, and excellent biocompatibility. The purpose of this study was to incorporate TAC in functionalized silica nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…However, Chen et al reported that SiO 2 NPs led to cytotoxicity, ROS generation, and DNA damage in the human cornea [ 15 ]. SiO 2 NPs can be used as intravitreal drug carriers [ 38 , 41 ]; however, to the best of our knowledge, the retinal toxicity of SiO 2 NPs has not been investigated before now. Therefore, we conducted both in vitro and in vivo experiments to evaluate the retinal toxicity of SiO 2 NPs with sizes of 15 and 50 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Chen et al reported that SiO 2 NPs led to cytotoxicity, ROS generation, and DNA damage in the human cornea [ 15 ]. SiO 2 NPs can be used as intravitreal drug carriers [ 38 , 41 ]; however, to the best of our knowledge, the retinal toxicity of SiO 2 NPs has not been investigated before now. Therefore, we conducted both in vitro and in vivo experiments to evaluate the retinal toxicity of SiO 2 NPs with sizes of 15 and 50 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Because the concentration of SiO 2 NPs used as a drug carrier was reported to be 100 μg/mL [ 38 ], we studied the in vivo retinal toxicity of SiO 2 NPs at a concentration of 80 μg/mL, which was the highest concentration used in our in vitro experiments. First, cell death and TUNEL assays were performed.…”
Section: Discussionmentioning
confidence: 99%
“…However, follow-up studies on ERGs indicated no changes in the retina cell function after 15 days of intravitreal injection, which were also proved by histopathologic examination, further supporting the biocompatibility, safety, and efficacy of the developed nanocarrier system in ocular therapy. Thus, the findings affirmed the considerable potential of MSNAPTES TAC to transport therapeutics in the ocular delivery for the treatment of eye diseases [ 53 ].…”
Section: Inorganic Npsmentioning
confidence: 55%
“…They evaluated the cell viability of MSNAPTES and TAC-loaded MSNAPTES (MSNAPTES-TAC) in the ARPE-19, and further, a chorioallantoic membrane (CAM) assay model was employed to show the biocompatibility and safety after intravitreal injection in vivo. Moreover, it was clinically examined based on measurement of intraocular pressure, ERG, and histopathological studies in rats’ eyes [ 53 ].…”
Section: Inorganic Npsmentioning
confidence: 99%
“…The scientists did not detect any systemic or organ side effects connected to the topic treatment following a 12 week observation period after particle administration. Intravitreally injected silica nanoparticles showed anti-angiogenic effects inhibiting VEGFR phosphorylation after VEGF binding [95], while in another study, they showed promising results for the ocular delivery of tacrolimus [96].…”
Section: Inorganic Nanoparticlesmentioning
confidence: 98%